Disease-specific anxiety symptomatology in Parkinson's disease. (10th February 2016) - Dissanayaka, Nadeeka N. W.; O'Sullivan, John D.; Pachana, Nancy A.; Marsh, Rodney; Silburn, Peter A.; White, Elizabeth X.; Torbey, Elizabeth; Mellick, George D.; Copland, David A.; Byrne, Gerard J.
ABSTRACT: Background: Symptoms of anxiety relating to Parkinson's disease (PD) occur commonly and include symptomatology associated with motor disability and complications arising from PD medication. However, there have been relatively few attempts to profile such disease-specific anxiety symptoms in PD. Consequently, anxiety in PD is underdiagnosed and undertreated. The present study characterizes PD-related anxiety symptoms to assist with the more accurate assessment and treatment of anxiety in PD. Methods: Ninety non-demented PD patients underwent a semi-structured diagnostic assessment targeting anxiety symptoms using relevant sections of the Mini International Neuropsychiatric Interview (MINI-plus). In addition, they were assessed for the presence of 30 PD-related anxiety symptoms derived from the literature, the clinical experience of an expert panel and the PD Anxiety-Motor Complications Questionnaire (PDAMCQ). The onset of anxiety in relation to the diagnosis of PD was determined. Results: Frequent (>25%) PD-specific anxiety symptoms included distress, worry, fear, agitation, embarrassment, and social withdrawal due to motor symptoms and PD medication complications, and were experienced more commonly in patients meeting DSM-IV criteria for an anxiety disorder. The onset of common anxiety disorders was observed equally before and after a diagnosis of PD. Patients in a residual group of Anxiety Not Otherwise Specified had an onset of anxiety after a diagnosis of PD. Conclusion: Careful characterization of PD-specific anxiety symptomatology provides a basis for conceptualizing anxiety and assists with the development of a new PD-specific measure to accurately assess anxiety in PD.